Sistem Informasi Inventory Berbasis Website Pada Toko Anugerah Sticker di Semarang - Grace Ivana; Marsiska Ariesta Putri; Prihati Prihati; Aji Priyambodo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to develop a web-based inventory information system to facilitate inventory data management and improve operational efficiency at Toko Anugerah Sticker. Currently, inventory management is still performed manually using paper, which complicates monitoring stock, recording incoming and outgoing items, and preparing reports accurately and promptly. To address these issues, the system was developed using the Waterfall method, consisting of five stages: requirement, design, implementation, verification, and maintenance. PHP was employed as the programming language for system development, while MySQL served as the database for storing inventory data. The system was tested using Blackbox testing to unsure that each function worked as expected. The result show that the web-based inventory information system successfully replaced the manual process, making inventory management more effective and efficient. It also enables real-time stock monitoring and generates reports faster and more accurately. The implementation of this system is expected to improve the quality of inventory data management at Toko Anugerah Sticker in the future.